2020
DOI: 10.1101/2020.07.07.191015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cis-regulatory chromatin loops arise before TADs and gene activation, and are independent of cell fate during development

Abstract: AbstractDuring development, naïve cells gradually acquire distinct cell fates, through sophisticated mechanisms of precise spatio-temporal gene regulation. Acquisition of cell fate is thought to rely on the specific interaction of remote cis-regulatory modules (e.g. enhancers, silencers) (CRM) and target promoters. However, the precise interplay between chromatin structure and gene expression is still unclear, particularly in single cells within multi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 97 publications
(162 reference statements)
1
12
0
Order By: Relevance
“…One possibility is that these putative enhancers are not as strong as the common ones and they might be missed by experimental methods. Alternatively, they might be primed enhancers [74], enhancers displaying most of the active marks, but not activating transcription yet. Based on our analysis, we cannot exclude that some of the putative enhancers are primed enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that these putative enhancers are not as strong as the common ones and they might be missed by experimental methods. Alternatively, they might be primed enhancers [74], enhancers displaying most of the active marks, but not activating transcription yet. Based on our analysis, we cannot exclude that some of the putative enhancers are primed enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even in the case when a promoter has a 3D contact with a regulatory sequence, less than 10% of genes display differential expression when the contact is lost, but the same is true at maintained loops. This suggests that the presence of chromatin loops would not be essential for controlling gene transcription in the majority of cases 58,[63][64][65] .…”
Section: Chromatin Loops and Gene Regulationmentioning
confidence: 99%
“…However, the dependency between chromatin architecture and transcription regulation in vivo is a matter of debate. For instance, contacts between cis-regulatory elements precede gene activation during Drosophila development and remain regardless of the transcriptional state [169]. A few studies also found that enhancer-promoter proximity is not always indicative of the transcriptional state [94,170].…”
Section: Future Directionsmentioning
confidence: 99%